Persekitaran Kerja Dan 'Burnout' Di Kalangan Guru Pendidikan Jasmani Dan Sukan - Lim , Khong Chiu (Penerbit Universiti Sains Malaysia, 2002)
The aim of this study was to evaluate burnout level among physical educators and sports' teachers (PJS) and its relation to work environment in schools. The adapted questionnaires from Fejgin et.al (1995) and Pines and Aronson (1981) were administered to 82 respondents. The results of the study showed that the PJS teachers had low level of bumout. A t-test analysis indicated that there was a significant difference in bumout level between the PJS teachers in primary and secondary schools.